2001
DOI: 10.1007/s11627-001-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteins related with embryogenic potential in callus and cell suspensions of sugarcane (Saccharum sp.)

Abstract: Previous results have shown that some proteins secreted in the culture medium are involved with the formation of embryogenic cells and can modify somatic embryo differentiation. Undifferentiated cell suspensions grown in the presence of 13 mM 2,4-dichlorophenoxyacetic acid (2,4-D) and obtained from embryogenic and non-embryogenic callus were used to study these events in sugarcane plants (cv. PR-62258). The cell suspension growth curves were determined and soluble proteins were extracted from embryogenic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…3d). Our result is similar to the observations of Oropeza et al (2001) and Nieves et al (2008) who detected more protein in embryogenic callus of Saccharum sp. in comparison to callus of non-embryogenic origin.…”
Section: The Influence Of Growth Regulators On Several Biochemical Pasupporting
confidence: 92%
“…3d). Our result is similar to the observations of Oropeza et al (2001) and Nieves et al (2008) who detected more protein in embryogenic callus of Saccharum sp. in comparison to callus of non-embryogenic origin.…”
Section: The Influence Of Growth Regulators On Several Biochemical Pasupporting
confidence: 92%
“…It was found that the 2.5-year-old callus of the KP-G genotype was composed of vacuolated cells devoid of cytoplasmic content, whereas the 6-month-old callus of the same genotype consisted of cells with dense cytoplasmic contents. Oropeza et al (2001) detected that, in sugarcane, the embryogenic callus contained densely cytoplasmic dividing cells with prominent nuclei, whereas the non-embryogenic callus contained vacuolated cells with sparse cytoplasm and few starch grains. They concluded that the embryogenic cells had a high metabolic activity with higher levels of proteins, mRNAs and other cytoplasmic components, whereas nonembryogenic cells had a low metabolic activity.…”
Section: Morphological Characteristicsmentioning
confidence: 98%
“…Few proteins associated with the somatic embryogenesis process have been identified and protein patterns were relatively stable during the culture (Hahne et al,1988;Ramagopal, 1989;Boyer et al, 1993;Oropeza et al, 2001). In this research, we found that there are several changes in protein patterns during the development of SEs.…”
Section: Article In Pressmentioning
confidence: 57%